Isolation and identification of pathogenic bacteria at riverbank filtration (RBF) study site: Lubuk Buntar, Kedah, Malaysia - Ghazali, Miskiah Fadzilah; Adzami, Nuraiffa Syazwi; Tajarudin, Husnul Azan; Mohd Arif Zainol, Mohd Remy Rozaini; Shoparwe, Noor Fazliani; Daud, Zawawi (UTHM Publisher, 2018)
River water is used for various purposes like as drinking water, in agriculture etc. The impact of river water pollution on human health depends mainly on the water uses, as well as the concentration of pathogen in water. Riverbank filtration (RBF) is an efficient and low-cost natural alternative filtration technology for water supply application. This technology was greatly removing many contaminants including pathogenic bacteria and viruses. However, this technology is new and not well explored in Malaysia. During the study, USM research team has embarked on the study of RBF at Lubuk Buntar, Kedah Malaysia. In order to understand the transportation of pathogenic bacteria during the filtration process, it is necessary to identify residence pathogenic bacteria in the river. Hence, this study was aimed to isolate and identify the pathogenic bacteria at the RBF study area located in Lubuk Buntar, Kedah, Malaysia. This study also conducted physicochemical test to monitor the river water quality. Analysis of 16S rDNA sequence revealed that Bacillus cereus ATCC 14579, Pseudomonas aeruginosa DSM 50071, Enterobacter ludwigii EN-149 were the origin pathogenic bacteria in the river at the RBF study site. pH for the river water was found in range 5.24-6.89 while temperature was recorded in range 30-25.31°C. BOD and COD were in range 6.8-2.0 mg/l and 31.0-8.0 mg/l respectively. The results show high value of turbidity, TSS and color which in range 179-64 mg/l, 177-68 and 74-20 PtCo respectively.